Scabies in Koranic schools in Dakar, Senegal: Comparison of two therapeutic modalities - Fatimata, Ly; Adama, Faye; Issa, Wone; Souleye, Lelo; Astou, Diouf; Abou, Koundio; Tene, Ndiaye Diop Mame; Fatou, Gueye Diagne; Aminata, Deh; Babacar, Faye; Oumar, Toure Fall Awa; Antoine, Mahé; Anta, Tall Dia (Public Health of Indonesia, 2021)
Background: In 2017, WHO recognized scabies as a neglected tropical disease. The optimal treatment is not well defined in some communities.Objective: This study aimed to compare ivermectin and benzyl benzoate in the treatment of scabies in Koranic schools (or "daara") in Dakar (region).Methods: This was a prospective randomized trial conducted from January to October 2018 in Senegal. Any resident living in the selected "daara" and diagnosed with scabies was included. The administered treatments were benzyl benzoate (BB) or ivermectin. At the outset, if one case of scabies was diagnosed, all residents received treatment. Ivermectin was given at the dose of 200 mg/kg. The same treatment was repeated on day 7 for each group, the endpoint was at D14, and the data were analyzed with STATA 14.Results: Fifteen "daara" were included. Of the 959 residents, 70 were diagnosed with scabies: prevalence of 7.29%. All patients except one were male; the mean age was 9.98 years (4-17). At D14, in the BB arm, cure rate was 42.85% (n = 15) while in the ivermectin arm, this rate was 5.71% (n = 2) with a significant difference (p = 0.01). On D28, the cure rate was still higher in the BB group 57.14 (n=20) versus ivermectin 21.42 (n = 6) with a significant difference (p = 0.004). On D42, all patients except eight were cured. At D14, we found a link between the cure rate, the number of people in the room (p = 0.01), and the number of showers per week (p = 0.01) but no link with the number of people per "daara" (p = 0.163). At D28, we found a link between the cure rate, the number of people sleeping in the room (p = 0.03), and the number of showers per week (p = 0.01) but not with the number of people per "daara" (p = 0.07).Conclusion: In Koranic schools, the cure rate is higher with benzyl benzoate compared to ivermectin.